PENERAPAN PERENCANAAN PAJAK MELALUI PENGADAAN ASET TETAP DALAM MENENTUKAN BEBAN SEWA DAN BEBAN KREDIT ASET UNTUK MENGHEMAT PENGELUARAN PAJAK PADA WPOP SEKAR DI DENPASAR - Sukasih, Ni Ketut (KRISNA: Kumpulan Riset Akuntansi, 2022)
The company’s Fixed assets had been conducted internally by cash purchases. Currently the company wants to do invest more by purchasing more vehicles, however they experienced a revenue decline problem so it was difficult to procure fixed assets through internal funding sources. The company also wants to minimize their income tax burden as minimum possible. The solution that this company could do are apply leasing and using bank credit from their external funding sources. The purposes of this study are to calculate the comparison of the income tax payments reduction with alternative fixed assets between leasing and bank credit; and to find out which alternatives of fixed assets that can minimize the income tax (Pph) paid by the WP Sekar company in 2020. The data of this study are quantitative and qualitative data. Data obtained by interviewing some people and collecting documentation. The analytical technique used is quantitative descriptive analysis technique. Quantitative descriptive analysis technique is used to describe, explain and provide information in the form of figures for the amount of income tax burden between the two alternatives. The difference in expenses that can reduce tax income between the two alternatives, namely between leasing and tax credits, tax planning is required to save the amount of tax to be paid.